GENDER RELATIONS IN THE LANDLESS WORKERS MOVEMENT - MST: PERSPECTIVES FROM THE DESIGN OF EDUCATIONAL MOVEMENT - Padua Sabia, Claudia Pereira de [UNESP]; Antonelli Marcelino Brabo, Tania Suely [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The study aims to identify of of the gender relations within the Landless Workers Movement (MST) and if the MST educational process has contributed to the actions and discussions on the topic. This work is part of a project entitled Theoretical and practical conceptions education and work in the MST and had the financing CNPQ. In this study, the methodology uses the qualitative approach and the bibliographical research, document and data collection. Data collection consisted of interviews with coordinators of schools in MST settlements and a former leader of the National Movement Gender Sector. As a result, we have identified the development of gender issues in the MST, some progress was made, for example, joint ownership, giving legally women the same rights of ownership and use of land and also the participation of women in 50% of all the Movement's political bodies which required great effort and enhanced process of forming the same. However, remains the great challenge of creating possibilities for greater equality in the division of work and opportunities for women landless.
Keywords: Gender; Education in MST; Social movements